Spinal Anaesthesia Versus Local Anaesthesia for Inguinal Hernia Repair: A Comparative Study - Jha, Vinay Kumar; Chaudhary, Sanjay; Sah, Rajesh Kumar; Karn, Amit (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: Inguinal hernioplasty is one of the most commonly performed operations worldwide. Local anaesthesia can be a preferred method in day-care surgeries as alternative to spinal anaesthesia for hernia repair, especially with regards to operative conditions, postoperative pain relief and complications as well as the less economic burden This study aims to determine the advantage of local anesthesia as compared to the spinal anesthesia. Materials and Methods: This was a prospective follow up study consisting of hundred and ten patients conducted after the ethical committee clearance. The patients posted for tension free lichtenstein elective hernioplasty were allocated to either of two groups, group A (n=55) were given local anaesthesia and patients in group B (n=55) were given spinal anaesthesia. The operative and postoperative pain score using visual analogue scale, duration of surgery and any other complications were recorded. Results: Time taken in local anesthesia was similar with spinal anaesthesia. Intraoperative pain was higher in local anesthesia than spinal anaesthesia. Post operatively pain was less in the local anesthesia than in spinal anaesthesia. Post operative complications were more in spinal anesthesia group such as urinary retention, headache, etc. Conclusions: Local anesthesia can be another good choice for inguinal hernia repair owing to its advantages and less complications. It can be reliably concluded that local anaesthesia can be a preferred method in day-care surgeries owing to its advantages of ease of administration, less complications and low economic burden.